Forecasting the ionospheric - Risal, Noreen Nabilla (2022)
The variability of ionospheric parameters depends on space weather disturbance, affecting communication, radar, and navigation systems’ performance. One of the most important ionospheric parameters is the critical frequency of the ionospheric